Point-of-care platelet function testing in patients undergoing PCI: between a rock and a hard place - van Werkum, J.W. (Bohn Stafleu van Loghum, 2007)
Since recent studies have linked an impaired response to antiplatelet therapy with a higher incidence of atherothrombotic events, the monitoring of the efficacy of antiplatelet therapy in the individual patient has attracted much attention. In the present report, we demonstrate that platelet function testing with several point-of-care assays results in ambiguous and conflicting results: some assays indicated that the patient’s platelets were insufficiently inhibited by clopidogrel whereas other assays reported an adequate response. Therefore, platelet function assays should not be used solely to guide treatment decisions, and tailor-made antithrombotic treatment has to wait for the most predictive platelet function test to emerge for measuring the risk for thrombotic complications after stenting. Until then, daily clinical practice should not be guided by point-of-care platelet function testing. (Neth Heart J 2007;15:299-305.18030318).